SETD1B-associated neurodevelopmental disorder. Issue 3 (16th June 2020) - Roston, Alexandra; Evans, Dan; Gill, Harinder; McKinnon, Margaret; Isidor, Bertrand; Cogné, Benjamin; Mwenifumbo, Jill; van Karnebeek, Clara; An, Jianghong; Jones, Steven J M; Farrer, Matthew; Demos, Michelle; et al.
Abstract : Background: Dysfunction of histone methyltransferases and chromatin modifiers has been implicated in complex neurodevelopmental syndromes and cancers. SETD1B encodes a lysine-specific methyltransferase that assists in transcriptional activation of genes by depositing H3K4 methyl marks. Previous reports of patients with rare variants in SETD1B describe a distinctive phenotype that includes seizures, global developmental delay and intellectual disability. Methods: Two of the patients described herein were identified via genome-wide and exome-wide testing, with microarray and research-based exome, through the CAUSES (Clinical Assessment of the Utility of Sequencing and Evaluation as a Service) Research Clinic at the University of British Columbia. The third Vancouver patient had clinical trio exome sequencing through Blueprint Genetics. The fourth patient underwent singleton exome sequencing in Nantes, with subsequent recruitment to this cohort through GeneMatcher. Results: Here we present clinical reports of four patients with rare coding variants in SETD1B that demonstrate a shared phenotype, including intellectual disability, language delay, conserved musculoskeletal findings and seizures that may be treatment-refractory. We include supporting evidence from next-generation sequencing among a cohort of paediatric patients with epilepsy. Conclusion: Rare coding variants in SETD1B can cause a diagnosable syndrome and could contribute as a risk factor for epilepsy, autism and other neurodevelopmental phenotypes. In the long term, some patients may also be at increased risk for cancers and other complex diseases. Thus, longitudinal studies are required to further elucidate the precise role of SETD1B in neurodevelopmental disorders and other systemic disease.